The straight to test endoscopy service for suspected colorectal cancer: meeting national targets but are we meeting our patients' expectations?. (August 2014) - Hitchins, C. R.; Lawn, A.; Whitehouse, G.; McFall, M. R.
Abstract Aim The NHS Cancer Plan describes initiatives to improve patient care in the UK, including the two‐week rule cancer referral pathway. To meet this target a straight to test (STT) endoscopy service was devised to expedite diagnosis of suspected colorectal cancer. Our novel study aimed to determine patient satisfaction with this new approach to rapid access investigation. Method An anonymized questionnaire was posted to 300 patients who had undergone STT endoscopy in our unit between January and June 2010. It assessed satisfaction with the service overall, time from referral to investigation, pre‐test information, bowel preparation instructions and time to results as well as preference for a traditional pre‐test or post‐test outpatient appointment and awareness that the referral was for suspected bowel cancer. Results In all, 174 questionnaires were obtained (58% yield; mean age 68.8; 44.8% men). 82.2% of patients were 'very satisfied' with the service overall, 82.8% with time from referral to test, 75.2% with time from test to results, 73% with endoscopy information and 69.5% with bowel preparation instructions. Eight per cent would rather have seen a specialist prior to endoscopy, 31.6% would have preferred a post‐test appointment and 68.4% of patients were aware that referral was for suspected bowel cancer. Conclusion Straight to test is popular with patients. It offers a fast and cost effective service in the diagnosis of colorectal cancer and meets national targets whilst reducing the volume burden on outpatient clinics. However, its success heavily relies on accurate communication between general practitioner, patient and secondary care.